2019
DOI: 10.12968/hmed.2019.80.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory management of acute decompensation in heart failure

Abstract: Heart failure is an increasingly prevalent chronic condition which causes substantial morbidity and mortality, placing an increasing economic burden on health care. Hospitalizations as a result of heart failure are projected to increase considerably over the next two decades. A robust restructuring of existing heart failure treatment models in the UK is needed to enable an integrated seamless transition of care across the community, primary care and hospital networks. This has to be achieved with the patient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…However, the admission rate for the HeartFailure@Home cohort is significantly lower than has been reported in previous studies. 5 , 7 , 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the admission rate for the HeartFailure@Home cohort is significantly lower than has been reported in previous studies. 5 , 7 , 26 …”
Section: Discussionmentioning
confidence: 99%
“… 4 In cases where self‐care or supervised up‐titration of oral diuretics have proved ineffective, evidence is growing to support the safe and effective administration of intravenous (IV) diuretics in a community setting. 5 , 6 , 7 Previous work has demonstrated that community‐based IV diuresis is cost‐effective and popular with patients. 6 Despite these findings, adoption of ambulatory IV diuretic therapy has not been widespread and has yet to be formally recommended in either European or North American guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…There is no clear evidence that hospitalization improves outcome. 32 Treatment with intravenous diuretics in an outpatient setting could represent a viable alternative strategy for hospitalization. Patients with worsening HF have relatively slow onset and progression of symptoms that provides a window during which outpatient treatment may relieve symptoms without the need for emergency department presentation or hospitalization.…”
Section: Safety and Efficacy Of Outpatient Treatment Of Worsening Hfmentioning
confidence: 99%
“…25 In the United States, approximately 19% of hospitals have the possibility of outpatient treatment with intravenous or subcutaneous diuretics, and these treatments comprise 1.4% of all outpatient visits for HF.. 31 Outpatient treatment of patients with worsening HF could avoid delays when presenting to the emergency department and streamline standard disciplinary HF care and early follow-up after treatment. 32 Furthermore, complications of hospitalization could be prevented, such as venous thrombosis, phlebitis, hospital-acquired pneumonia, ulcers due to lack of mobility, loss of control, and depression, estimated to be as high as 25%. 34 Risk stratification and clinical decision making: choosing the right patient and right treatment for outpatient treatment of worsening HF…”
Section: Safety and Efficacy Of Outpatient Treatment Of Worsening Hfmentioning
confidence: 99%
See 1 more Smart Citation